GeneCaRNA: A Comprehensive Gene-centric Database of Human Non-coding RNAs in the GeneCards Suite. Issue 11 (28th May 2021) - Barshir, Ruth; Fishilevich, Simon; Iny-Stein, Tsippi; Zelig, Ofer; Mazor, Yaron; Guan-Golan, Yaron; Safran, Marilyn; Lancet, Doron
Graphical abstract: Highlights: Lack of comprehensive gene-centric ncRNA database for non-coding variant scrutiny. The GeneCaRNA database is an all-inclusive compendium of non-coding RNA genes. GeneCaRNA provides an effective search leveraging annotations from 178 data sources. GeneCaRNA data are visualized by a UCSC hub and empower ncRNA interaction networks. GeneCaRNA provides a potent whole genome sequencing disease interpretation tool. Abstract: Non-coding RNA (ncRNA) genes assume increasing biological importance, with growing associations with diseases. Many ncRNA sources are transcript-centric, but for non-coding variant analysis and disease decipherment it is essential to transform this information into a comprehensive set of genome-mapped ncRNA genes. We present GeneCaRNA, a new all-inclusive gene-centric ncRNA database within the GeneCards Suite. GeneCaRNA information is integrated from four community-backed data structures: the major transcript database RNAcentral with its 20 encompassed databases, and the ncRNA entries of three major gene resources HGNC, Ensembl and NCBI Gene. GeneCaRNA presents 219, 587 ncRNA gene pages, a 7-fold increase from those available in our three gene mining sources. Each ncRNA gene has wide-ranging annotation, mined from >100 worldwide sources, providing a powerful GeneCards-leveraged search. The latter empowers VarElect, our disease-gene interpretation tool, allowing one to systematically decipher ncRNA variants. The combined power of GeneCaRNA with GeneHancer, our regulatory elements database, facilitates wide-ranging scrutiny of the non-coding terra incognita of gene networks and whole genome analyses.